(Un)safe Space in the Borderlands: Writing Queer Women of Color into History - Thayse Madella (Ilha do Desterro)
This article intends to analyze how Xicana literature navigates (un)safe spaces in the Borderlands. As women, who, more often than not, are also queer, the literature of Xicana authors constantly struggles to find safe spaces in the Borderlands. The historical novel Forgetting the Álamo (2009), by Emma Pérez, illustrates the mobilization of spaces into (un)safe ones. The novel, by remembering the presence of queer Xicanas in history (in the aftermath of the battle of the Alamo), constructs (un)safe spaces in a constantly changing geographical location. The pervasiveness of coloniality is always already endangering the safety of one’s existence. The instability of these “safe spaces” renders them, at the same time, unsafe. This paradoxical relationship opens the possibility of the fractured locus, where colonial and non-colonial discursive practices meet and are rearticulated.